Improving Pedagogic Competence through Learning Videos - Herlina Herlina (JME (Journal of Mathematics Education), 2020)
The purpose of this study was to improve learning outcomes in the subjects of Basics and Mathematics Learning Process. This study uses a pre-experimental one group pre post design. The research subjects are prospective student teachers who take the Basics and Mathematics Learning Process course consisting of 41 students in 2020. The instrument used is a test instrument that is given before and after treatment in the form of pretest and posttest. Data analysis used two mean differences, namely paired two sample t-test, but previously tested for normal distribution using Kolmogorof Sminov. To see the improvement in learning outcomes, both data were analyzed by N-Gain. The results of the descriptive analysis showed that the average pretest and posttest were different where the posttest average was 77.44 higher than the pretest average was 62.68. The results of the two-average difference test show a significance value (2 tailed) (0,000) < ? (0.05), which means that the average pretest and posttest are significantly different. The results of the N-Gain calculation show that the increase in learning outcomes is included in the medium category, so that an increase in learning outcomes is obtained Based on the results of the study, it was concluded that the use of instructional video media can improve learning outcomes for the Basic Learning Process and Mathematics courses. This is possible because videos about learning can represent teaching simulations more than just lectures or discussions.